Reconstruction Reconstruction of Mining Permitting Policies Based on Water Resource Protection: A Study of PDAM Water Pollution in Bangka Regency - Yusrizal, Yusrizal; Saliman, Abdul Rasyid (Dinasti Research, 2025)
This research examines the problematic mining licensing policies in Bangka Regency concerning the protection of water resources as part of fulfilling citizens' constitutional rights. Mining activities in this region have contributed to the contamination of water sources managed by the Regional Water Company (PDAM), which has implications for the fulfillment of the right to clean water as guaranteed in the 1945 Constitution. Using a juridical-empirical approach, this study analyzes the fundamental weaknesses in the mining licensing policy framework that has not integrated water resource protection as a primary consideration. The research findings indicate that the mining licensing process emphasizes economic aspects and pays less attention to ecological impacts on water sources, resulting in a conflict between economic interests and the fulfillment of constitutional rights. This research proposes a reconstructed model of mining licensing policy that integrates impact assessments on water resources, establishment of water source protection zones, and mechanisms for accountability and compensation for pollution. Through this policy reconstruction, it is expected to create a balance between the utilization of natural resources for economic development and the protection of citizens' constitutional rights to clean water in Bangka Regency.